Memory and Amnesia in the Presentation of the Hanamatsuri of Aichi Prefecture, Japan - Kuly, Lisa (Acta Orientalia Vilnensia, 2006)
Cornell University The Hanamatsuri is a complex ritual presented by around 17 communities located around a tributary system flowing into the Tenryû River which runs through the prefectures of Shizuoka, Nagano, and Aichi in Japan. It is associated with the end of the year, the New Year, and the revitalization of the world. Mapping the local onto the national is a significant concern that has been generated out of this festival. Maintaining a discourse of authenticity is another concern. These issues are set within a postmodern framework, as the author illustrates how elements of Japan’s postmodernism filtered down to the communities which perform the Hanamaturi. In a larger sense, this paper participates in the academic inquiry in Japanese religious studies into how ritual and popular religion contribute to the construction of cultural memory.